2012
DOI: 10.1002/adfm.201102930
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive, Biocompatible, Quantum‐Dot‐Embedded Silica Nanoparticles for Bioimaging

Abstract: The successful development of highly sensitive, water‐compatible, nontoxic nanoprobes has allowed nanomaterials to be widely employed in various applications. The applicability of highly bright quantum dot (QD)‐based probes consisting of QDs on 120 nm silica nanoparticles (NPs) with silica shells is investigated. Their substantial merits, such as their brightness and biocompatibility, for effective bioimaging are demonstrated. Silica‐coated, QD‐embedded silica NPs (Si@QDs@Si NPs) containing QDs composed of CdS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
106
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 30 publications
3
106
0
Order By: Relevance
“…In 2012, Jun et al reported an ultrasensitive QDs-embedded SiNP for tumor fluorescence imaging (Figure 2a). 73 Compared to a single QD, the QDs-embedded SiNPs showed brighter fluorescence intensity and increased uptake by HeLa cells (Figure 2b). For in vivo fluorescence cell tracking, single QD labeled- or QDs-embedded SiNPs labeled-HeLa cells were injected into mice for long-term fluorescence imaging, and the results showed that even after 10 days, the QDs-embedded SiNPs emitted strong fluorescence for in vivo imaging (Figure 2c).…”
Section: Imaging Applications Of Silica Nanoparticlesmentioning
confidence: 97%
“…In 2012, Jun et al reported an ultrasensitive QDs-embedded SiNP for tumor fluorescence imaging (Figure 2a). 73 Compared to a single QD, the QDs-embedded SiNPs showed brighter fluorescence intensity and increased uptake by HeLa cells (Figure 2b). For in vivo fluorescence cell tracking, single QD labeled- or QDs-embedded SiNPs labeled-HeLa cells were injected into mice for long-term fluorescence imaging, and the results showed that even after 10 days, the QDs-embedded SiNPs emitted strong fluorescence for in vivo imaging (Figure 2c).…”
Section: Imaging Applications Of Silica Nanoparticlesmentioning
confidence: 97%
“…Due to previously known benefits of silicon, like reduced elemental toxicity, its potential biodegradability to silicic acid and its abundance and low costs are adding to the promising results of recent investigations that indicate silicon use in in vivo imaging to be a good alternative to cadmium QDs [13,14]. Nanoporous and microparticulate forms of silicon have shown great promise in terms of compatibility and cytotoxicity [15]. Nonetheless, studies concerned with the biological and medical applications of silicon-based QDs are less numerous and still at preliminary stages [16-18].…”
Section: Introductionmentioning
confidence: 99%
“…The high efficient assembly of hydrophobic QDs with metal-affinity substrates via coordination chemistry (Lu et al, 2011), provides a promising alternative to improve QDs loading density and optical properties (Jun et al, 2012), compared with aqueous phase layer-by-layer assembly technics (Bakalova et al, 2008). Silicon, a versatile and biocompatible material for both substrates and coating layers on nano-objects (Jana et al, 2007;Foda et al, 2014), exhibits unique process ability that enabling facile incorporation of noble metal nanoparticles and a variable space between the plasmonic interior and surface attached fluorophores (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%